21st Century Geopolitical Doctrine for Bangladesh to Become a Smart Power: A Bangladeshi Perspective - Hossain, Md. Kazi Rezuan; Hoque, Md. Selimul (International Journal of Social Sciences and Management, 2024)
After a grueling nine-month conflict with Pakistan, Bangladesh gained independence as a sovereign nation on December 16, 1971. The economically successful South Asian nation that was previously known as the "bottomless basket" has become known as a "development miracle." The country has regained geopolitical significance both within and outside the area due to its proximity to other countries and strategic location, which has been supported by astounding economic development. Bangladesh is faced with several geopolitical issues amid a changing regional and global geopolitical scene, the mitigation of which calls for prudent actions. But Bangladesh, as a contemporary geopolitical actor, lacks a wise geopolitical philosophy that could serve as a guide for dealing with those problems. This study proposes the creation of a coherent and pertinent geopolitical ideology that can help a nation achieve geopolitical graduation as a Smart Power and address current geopolitical issues shortly.Int. J. Soc. Sc. Manage. Vol. 11, Issue-4: 106-114.